Steroid cell ovarian tumor: A case report of an unusual condition - Sharma, Paban Kumar; Joshi, Sujan (Nepal Journal of Obstetrics and Gynaecology, 2010)
A young girl presented with a solid pelvic tumor, was found to be steroid cell tumor of ovary, is described here because of its rarity and its association with unexplained anemia which was spontaneously corrected after the tumor removal. Ovarian steroid cell tumor is known to account for approximately 0.1% of all ovarian neoplasms and is unfortunately seen to exerts malignant potentials although its association with multiple different endocrine or paraneoplastic changes are the main issues with affection to women of young as well. Key words: Steroid cell tumor; lipoid tumor. DOI: 10.3126/njog.v4i1.3334 Nepal Journal of Obstetrics and Gynaecology June-July 2009; 4(1): 52-54